1991
DOI: 10.1016/0014-5793(91)80519-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of glycolipid receptors for Helicobacter pylori by TLC‐immunostaining

Abstract: H¢lic~baeter pylorl has I~en identified as a ¢~ttaati~ a=enl in ,ctiw chronic $astritis, The rec=ptor for this baeteri=t, however, is not known, It is likely that the r~wptor molecules may b~ 81yt:osphinsolipid~.* as shown in th~ ea~cs orother bacteria. We explored this po~sihility by a thin-layer chromatography (~LC).immun~staininu method. Amontt lllyeo~phinllolipids extracted from hum;tn gastric mucosa, intact t1¢11¢.oba¢l¢t pylorl Sl~.cifleall~, bound to PSO~.O~tleer trod IPNeuAc.LacCer. whereas no specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
71
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(75 citation statements)
references
References 15 publications
2
71
2
Order By: Relevance
“…Therefore, interest has been directed to the elucidation of receptors for different microorganisms, many of which have been demonstrated to be glycosphingolipids (14,25). Initial studies of potential receptors for H. pylori suggested that acid glycosphingolipids, such as the GM3 ganglioside and sulfatide (7,27), can function as receptors for the bacterium. (The glycosphingolipid nomenclature follows the recommendations of the International Union of Pure and Applied Chemistry-International Union of Biochemistry Commission on Biochemical Nomenclature [Commission on Biochemical Nomenclature for Lipids] [5a, 5b, 5c].…”
mentioning
confidence: 99%
“…Therefore, interest has been directed to the elucidation of receptors for different microorganisms, many of which have been demonstrated to be glycosphingolipids (14,25). Initial studies of potential receptors for H. pylori suggested that acid glycosphingolipids, such as the GM3 ganglioside and sulfatide (7,27), can function as receptors for the bacterium. (The glycosphingolipid nomenclature follows the recommendations of the International Union of Pure and Applied Chemistry-International Union of Biochemistry Commission on Biochemical Nomenclature [Commission on Biochemical Nomenclature for Lipids] [5a, 5b, 5c].…”
mentioning
confidence: 99%
“…Several different binding specificities of H. pylori have previously been demonstrated. Thus, the binding of the bacterium to such diverse compounds as phosphatidylethanolamine and gangliotetraosylceramide (7), the Le b blood group determinant (8), heparan sulfate (9), the GM3 1 ganglioside and sulfatide (10,11), and lactosylceramide (12), has been reported. A sialic aciddependent binding of H. pylori to large complex glycosphingolipids (polyglycosylceramides) has also been documented (13).…”
mentioning
confidence: 99%
“…The (28). Recently, Saitoh et al (42) identified both an NL-containing moiety (GM3-ceramide) and sulfated lactosylceramide as H. pylon receptors that are present in human gastric mucosa; their results indicated the existence of two different H. pylon ligands corresponding to these two receptors.…”
mentioning
confidence: 99%